CYFIP family proteins between autism and intellectual disability: links with Fragile X syndrome - Bardoni, Barbara; Abekhoukh, Sabiha (Frontiers in Cellular Neuroscience, 2014)
Intellectual disability (ID) and autism spectrum disorders (ADS) have in common alterations in some brain circuits and brain abnormalities, such as synaptic transmission and dendritic spines morphology. Recent studies have indicated a differential expression for specific categories of genes as a cause for both types of disease, while an increasing number of genes is recognized to produce both disorders. An example is the Fragile X Mental retardation gene, FMR1, whose silencing causes the Fragile X syndrome, the most common form of intellectual disability and autism, also characterized by physical hallmarks. FMRP, the protein encoded by FMR1, is an RNA-binding protein with an important role in translational control. Among the interactors of FMRP, CYFIP1/2 proteins are good candidates for intellectual disability and autism, on the bases of their genetic implication and functional properties, even if the precise functional significance of the CYFIP/FMRP interaction is not understood yet. CYFIP1 and CYFIP2 represent a link between Rac1, the Wave complex and FMRP, favoring the cross talk between actin polymerization and translational control